2012
DOI: 10.2519/jospt.2012.4142
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Thoracic Spine Manipulation in Subjects With Signs of Rotator Cuff Tendinopathy

Abstract: Rotator cuff tendinopathy (RCT) is one of the most common causes of shoulder pain and dysfunction 5,26,48,73,74 and has been associated with symptoms of shoulder impingement. 15 While TSM may be beneficial in reducing shoulder pain and dysfunction, the mechanisms by which the manipulation might induce these changes are not well understood. Bialosky et al 3 suggested that the introduction of a manipulative force results in biomechanical as well as neurophysiologic responses. Biomechanical re-T T STUDY DESIGN: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
92
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(107 citation statements)
references
References 79 publications
(86 reference statements)
9
92
3
1
Order By: Relevance
“…Thrust manipulation techniques seemed to show immediate effect in studies not using a control intervention, [13,22,25,26], but were not superior when compared to sham manipulation [23,24]. Of these studies, only Mintken et al examined pain and shoulder ROM as outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thrust manipulation techniques seemed to show immediate effect in studies not using a control intervention, [13,22,25,26], but were not superior when compared to sham manipulation [23,24]. Of these studies, only Mintken et al examined pain and shoulder ROM as outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Studies, using single or short interventions to the thoracic spine and the upper ribs show conflicting immediate- [22][23][24]26] and short-term results [13,25] in patients with shoulder pathology. Thrust manipulation techniques seemed to show immediate effect in studies not using a control intervention, [13,22,25,26], but were not superior when compared to sham manipulation [23,24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There were 77 full-text articles screened (26 SRs and 51 RCTs). Eight were excluded as follows: 1 systematic review was outside the scope of this review (it did not include RCTs of shoulder conditions), 23 leaving 25 SRs; 5 articles designated as RCTs did not actually meet the definition of an RCT (did not test efficacy or did not test between-group differences) [24][25][26][27][28] ; and 2 were outside the scope of our review (1 did not measure patient-based outcomes, 29 and the other was a prognostic study 30 ), leaving 44 RCTs. The research question was clearly defined and the inclusion/exclusion criteria listed in the paper (if "no," then reject).…”
Section: Data Extractionmentioning
confidence: 99%
“…6,7,16,17 In addition, recent studies have reported improvements in patient`s rated pain and function after a single treatment of thoracic SMT in patients with subacromial impingement syndrome, but they did not find mechanical changes in thoracic spine or shoulder mobility. 14,18 However, none of these studies included a symptomatic or asymptomatic control group for comparison in the controlled trials. Furthermore, no studies included cervicothoracic mobilization with and without impulse technique and exercise therapy in low cervical spine for the upper thoracic spinal dysfunction in SIS.…”
Section: Introductionmentioning
confidence: 99%